ANALISIS PENGELOLAAN PENDAPATAN ASLI DAERAH DAN KONTRIBUSINYA PADA APBD KABUPATEN TANA TORAJA - Paulus Tangke (PROGRESS, 2013)
This study is a case study conducted in Tana Toraja. This study aims to find out how the Management of Regional Original Revenue and Budget Expenditure Contribution In Tana Toraja Regency fiscal year 2010 to 2012. The method used in this research is to conduct field research conducted directly on the object of research in the form of direct interviews with the parties related to the writing of this research .The results of analysis of financial ratios showed a tendency to increase the effectiveness and efficiency in the aspect, when viewed from the aspect of managing the growth of local revenue decline in Tana Toraja experiencing significant growth, while the aspect of contribution shows still large dependence of the local government financial assistance from the government center. Tana Toraja Regency Government's ability to use local revenue to finance Revenue Expenditure Budget has not been too effective. This shows the government is still dependent on the use of funds from central to local budget financing.